Characterization of Pyroptosis-Related Subtypes via RNA-Seq and ScRNA-Seq to Predict Chemo-Immunotherapy Response in Triple-Negative Breast Cancer - Li, Chenlu; Pan, Jingjing; Jiang, Yinyan; Wu, Yanzhi; Jin, Zhenlin; Chen, Xupeng (Frontiers in Genetics, 2022)
Triple-negative breast cancer (TNBC) was usually associated with poor prognosis and invalid therapeutical response to immunotherapy due to biological heterogeneity. It is urgent to screen reliable indices especially immunotherapy-associated biomarkers that can predict outcomes of these patients. As an inflammatory form of programmed cell death, pyroptosis has been demonstrated to create a tumor-suppressive environment and raise the response to chemotherapeutic drugs in multiple tumors. However, the effect of pyroptosis on the therapeutical response and prognosis of TNBC remains unclear. In this study, we presented a consensus clustering by pyroptosis-related signatures of 119 TNBC patients into two subtypes with distinct immunological and prognostic characteristics. The clusterB, associated with better outcomes, was characterized by significantly higher pyroptosis-related signatures expression, tumor microenvironment (TME) scores, and up-regulation of immunotherapy checkpoints. A total of 262 different expression genes (DEGs) between subtypes were further identified and the Ps-score was built using LASSO and COX regression analysis. External GEO dataset demonstrated that low Ps-score cohorts were consistent with higher expression of pyroptosis-related signatures, immunocytic infiltration levels and better prognosis. In addition, external immunotherapy and chemotherapy cohorts validated the patients with lower Ps-scores exhibited significant therapeutic responses and clinical benefits. Combined with other clinical characteristics, we successfully constructed a nomogram to effectively predict the survival rate of TNBC patients. Finally, using the scRNA-seq datasets, we validated the landscape of cellular subtypes of TNBC and successfully constructed the miRNA-Ps-score genes interaction network. These findings indicated that the systematic assessment of tumor pyroptosis and identification of Ps-scores had crucial clinical implications and facilitated tailoring optimal immunotherapeutic strategies for TNBC.